2015
DOI: 10.1186/s40169-015-0057-2
|View full text |Cite
|
Sign up to set email alerts
|

Utility of five commonly used immunohistochemical markers TTF‐1, Napsin A, CK7, CK5/6 and P63 in primary and metastatic adenocarcinoma and squamous cell carcinoma of the lung: a retrospective study of 246 fine needle aspiration cases

Abstract: Background Fine needle aspiration (FNA) biopsy plays a critical role in the diagnosis and staging of lung primary and metastatic lung carcinoma. Accurate subclassification of adenocarcinoma (ADC) and/or squamous cell carcinoma (SqCC) is crucial for the targeted therapy. However, the distinction between ADC and SqCC may be difficult in small FNA specimens. Here, we have retrospectively evaluated the utility of TTF-1, Napsin A, CK7, P63 and CK5/6 immunohistochemical (IHC) markers in the distinguishi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 53 publications
9
60
0
Order By: Relevance
“…These biomarkers have different sensitivities and specificities. Our studies and others' studies have demonstrated that these markers have sensitivities and specificities ranging from approximately 70-100% for the identification of ADCs, and from approximately 60-100% for the identification of SqCCs [7,8]. Limitations of these biomarkers include: the requirement of multiple tissue sections for IHC study, which may exhaust tumor tissue, compromising the molecular characterization of the tumor in small biopsy samples; the time-consuming nature of IHC testing, which can result in prolonged turnaround times, significantly affecting the patient's clinical management; the interpretation of the IHC results may be influenced by nonspecific staining of non-neoplastic cells, such as, pulmonary alveolar macrophages and bronchial basal cells; and different clones of the same antibody may have different effects on the IHC staining pattern.…”
Section: Limitations Of Current Ihc Markerssupporting
confidence: 59%
See 1 more Smart Citation
“…These biomarkers have different sensitivities and specificities. Our studies and others' studies have demonstrated that these markers have sensitivities and specificities ranging from approximately 70-100% for the identification of ADCs, and from approximately 60-100% for the identification of SqCCs [7,8]. Limitations of these biomarkers include: the requirement of multiple tissue sections for IHC study, which may exhaust tumor tissue, compromising the molecular characterization of the tumor in small biopsy samples; the time-consuming nature of IHC testing, which can result in prolonged turnaround times, significantly affecting the patient's clinical management; the interpretation of the IHC results may be influenced by nonspecific staining of non-neoplastic cells, such as, pulmonary alveolar macrophages and bronchial basal cells; and different clones of the same antibody may have different effects on the IHC staining pattern.…”
Section: Limitations Of Current Ihc Markerssupporting
confidence: 59%
“…In daily clinical practice, the most commonly used IHC biomarkers are TTF-1, napsin A, mucin, CK5/6, P63 and P40 for the classification of NSLCLs [7,8].…”
Section: Limitations Of Current Ihc Markersmentioning
confidence: 99%
“…CEACAM1 is a necessary and limiting factor in the mechanism of the angiogenesis, since the new generation of capillaries cold be hardly completed with CEACAM1 [22]. Endothelium-derived nitric oxide (NO) as a critical regulator of vascular function was over-produced by the stimulation of VEGF via PI3K/Akt-dependent endothelial NO synthase (eNOS) activation [23]. VEGF failed to mediate eNOS activation and production without the existence of CEACAM1 [24].…”
Section: Roles Of Ceacam1 In Angiogenesismentioning
confidence: 99%
“…Nonsmall cell lung cancer, with the introduction of new treatment modalities, recognition and differential diagnosis between adenocarcinoma and squamous cell carcinoma is necessary for effective molecular target-specific treatments (2,3). Targets include epidermal growth factor receptors (EGFR), tyrosine kinase inhibitors (TKIs), and echinoderm microtubule associated protein-like 4-anaplastic lymphoma kinase (EML4-ALK) fusion protein (4).…”
Section: Introductionmentioning
confidence: 99%